2019
DOI: 10.1155/2019/2986286
|View full text |Cite
|
Sign up to set email alerts
|

Palivizumab Prophylaxis among Infants at Increased Risk of Hospitalization due to Respiratory Syncytial Virus Infection in UAE: A Hospital-Based Study

Abstract: Background. Respiratory syncytial virus (RSV) represents a significant public health burden and the leading cause of lower respiratory tract infections globally, and it is the major cause of hospitalization during the winter. We aimed to evaluate the effectiveness of palivizumab prophylaxis to reduce the hospitalization in children at high risk of RSV infection. Methods. We performed a retrospective observational single-arm hospital-based study including five RSV seasons (September to March) from 2012 to 2017.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
(34 reference statements)
1
2
0
Order By: Relevance
“…For the 21 hospitalized patients, the average stay was 7.42 ± 3.05 days, but the risk was higher in those with RSV infection; additionally, those born at a gestational age of less than 32 weeks had a significantly longer stay. These findings are very similar to those reported in the literature 19,20 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For the 21 hospitalized patients, the average stay was 7.42 ± 3.05 days, but the risk was higher in those with RSV infection; additionally, those born at a gestational age of less than 32 weeks had a significantly longer stay. These findings are very similar to those reported in the literature 19,20 …”
Section: Discussionsupporting
confidence: 92%
“…These findings are very similar to those reported in the literature. 19,20 When evaluating the risk factors that could be associated with patients admitted due to ALRI, BPD (OR: 1. were associated with an increased risk of visiting the ER for respiratory symptoms. Furthermore, it was found that the presence of positive RSV in the nasopharyngeal aspirate, supplemental oxygen therapy at home, and the presence of smokers at home were significantly associated with hospitalization for ALRI.…”
Section: Discussionmentioning
confidence: 99%
“…Compliance with the prophylaxis regimen is essential for effectiveness, 49,50 including appropriate timing of administration with respect to the RSV season, 51 and the need to consider extended coverage in some very high-risk individuals. 52 In a descriptive single-centered study over five RSV seasons from 2012 to 2017, Elhalik et al 53 enrolled 925 infants eligible for palivizumab immunoprophylaxis under AAP 2009 criteria. 54 Of these, 515 infants were born at 32 to 35 wGA.…”
Section: Compliancementioning
confidence: 99%
“…O vírus sincicial respiratório (VSR) é um vírus de RNA de fita simples, envelopado, negativo e não-segmentado, pertencente à família Pneumoviridae (ELHALIK et al, 2019), que acomete o trato respiratório em crianças, principalmente entre a faixa etária de 0 a 5 anos (FEROLLA et al, 2019). A infecção pelo vírus sincicial respiratório pode acometer o trato respiratório superior (GAREGNANI et al, 2021) e o inferior, sendo este a principal causa de hospitalização entre as crianças menores de um ano de idade (VIGÚRIA et al, 2021).…”
Section: Introductionunclassified